Literature review: Quality of life of patients with implanted devices for permanent cardiac pacing - Wojarska, Izabela Kamila (Journal of Education, Health and Sport, 2017)
The implantation of devices for permanent cardiac pacing is becoming more and more popular medical treatment for cardiac disorders. There are several types of devices that can be implanted into patients: pacemakers (PM), implantable cardioverter – defibrillators (ICD) and cardiac resynchronization therapy devices (CRT). All of the above-mentioned devices improve the quality of life and affect the survival. The quality of life is now considered as a significant purpose of treatment of patients with a cardiovascular disease. Surveys on the quality of life are especially useful to cardiac patients as they allow for conducting an overall assessment of their mental and physical state, the quality of life and the effectiveness of the treatment. In the available scientific literature, there are numerous analyses and data on the quality of life of patients with a cardiac pacemaker in different areas of its functionality. The presented review features research projects that measured the quality of life in various respects, e.g. limitations related to poor physical health, the impact of physical activity on everyday life, pain, general perception of health, emotional state and its impact on everyday life, limitations related to emotional problems or to physical health, mental health, vitality, and any issues related to the treatment of cardiac arrhythmias through the implantation of cardiac stimulation devices. In the earliest publications the numbers of participants were very low and thus the results may have been uncertain. However, more recent publications include sufficient number of participants to formulate general conclusions on the quality of life in the overall study population. The quality of life after implantation has improved significantly.